Assembling deviation estimation based on the real mating status of assembly. (October 2019) - Sun, Qingchao; Zhao, Binbin; Liu, Xin; Mu, Xiaokai; Zhang, Yuanliang
Abstract: The assembly precision of mechanical products is closely related to the morphology of the mating surface. In order to predict the assembly accuracy of high precision mechanical products efficiently, a calculation method of assembly deviation based on the real mating status is proposed. Firstly, the wavelet transform is used to decompose and reconstruct the mating surface morphology. Secondly, the two basic principles of the contact points of the mating surface are analyzed, and the virtual assembly model based on difference surface is established. Finally, the centroid-driven algorithm is proposed to calculate the real mating status, and the assembly deviation based on the mating status is characterized by small displacement torsors (SDT). By comparing the results of theoretical calculation and numerical analysis, the contact point position obtained by the two methods is almost consistent and the calculation error of assembly deviation is 6.83%. In addition, the centroid-driven algorithm has greatly improved the efficiency of assembly deviation estimation. In the assembly process of high-precision mechanical system, the content of this article can realize the accurate prediction of assembly deviation. Highlights: The wavelet transform theory is used to process the mating surface morphology. The centroid-driven algorithm is proposed to calculate the real mating status. This article realized the accurate and efficient prediction of assembly deviation.